Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
The 24th International Electronic Conference on Synthetic Organic Chemistry 2020
DOI: 10.3390/ecsoc-24-08380
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition of Thiourea- and Guanidine-Substituted Furans to Dienophiles: A Comparison of the Environmentally-Friendly Methods

Abstract: The cycloaddition strategy was employed in order to obtain a 7-oxanorbornene framework substituted with a guanidine moiety or its precursor functional groups: protected amine or thiourea. In order to optimize the conditions for the cycloaddition, several environmentally-friendly methods—microwave assisted organic synthesis, high pressure synthesis, high speed vibrational milling, and ultrasound assisted synthesis—were employed. The outcomes of the cycloaddition reactions were interpreted in terms of endo/exo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…We should emphasize that maleate derivative could also be formed but we limited our analysis to the formation of the more stable chlorofumarate 9 for the sake of simplicity. Deprotonation of the guanidinium cation by the chloride or iodide anion could be disregarded because we have shown that no aza-Michael addition products were obtained when N-phenylmaleimide was used instead of DMAD [25]. In this context, we could also note that the gas-phase basicities (GB) of 2-chlorofumarate and 2-chloromaleate anions calculated using B3LYP (1477 and 1469 kJ mol −1 , respectively) are significantly higher than that of chloride anions (1388 kJ mol −1 ; experimental value is 1374 kJ mol −1 [26]).…”
Section: Resultsmentioning
confidence: 99%
“…We should emphasize that maleate derivative could also be formed but we limited our analysis to the formation of the more stable chlorofumarate 9 for the sake of simplicity. Deprotonation of the guanidinium cation by the chloride or iodide anion could be disregarded because we have shown that no aza-Michael addition products were obtained when N-phenylmaleimide was used instead of DMAD [25]. In this context, we could also note that the gas-phase basicities (GB) of 2-chlorofumarate and 2-chloromaleate anions calculated using B3LYP (1477 and 1469 kJ mol −1 , respectively) are significantly higher than that of chloride anions (1388 kJ mol −1 ; experimental value is 1374 kJ mol −1 [26]).…”
Section: Resultsmentioning
confidence: 99%
“…Derivative 15 was obtained by base-catalyzed cyclization of the corresponding oxanorbornadiene [35]. Cycloadditions of N-Boc-furfurylamine with maleic anhydride and N-phenylmaleimide were conducted mechanochemically [50] and the analytical data for adduct 22 are identical to those prepared according to the literature [51]. The details are given in the Supplementary Materials.…”
Section: Methodsmentioning
confidence: 99%